Evaluation of settlement behavior of the improved ground by using floating type columns during consolidation - Z. B. Jiang; R. Ishikura; N. Yasufuku (Lowland Technology International, 2015)
For soft soil engineering, in many cases, the foundation directly on natural ground cannot satisfy the requirement, such as embankment on deep soft clay layer. Consequently, a technology of combining the float-type cement-treated columns and surface stabilization is developed for reducing the settlement and the construction cost. In order to apply this technology for practice, it is important to predict the total settlement of the ground in relation to the important factors. In this paper, in order to evaluate the consolidation settlement behavior, a time-dependent skin friction model for the columnsoil interaction is developed to describe the nonlinear relationship between column shaft shear stresses and effective vertical pressure in the surrounding soft clay. The timedependent equivalent skin friction length which treating a part of floating type improved ground with a length of αH1 as an unimproved portion can be obtained based on a homogenization theoretical method. The compression settlement of this unimproved portion can be computed using the properties of soft clay alone. For verifying the effectiveness of this method, a set of laboratory model tests were performed. Furthermore, the settlement behavior and stress distribution characteristics were investigated by image analysis.